Application of a Transportation Flux for Determining Qualitative Indices - Aleksander Nieoczym (Communications - Scientific letters of the University of Zilina, 2005)
A method of using the transportation flux of a manufacturing system for determining its qualitative parameters has been presented. Those subjects were discussed in many papers [1 – 4], however the presented method may be used for a preliminary determination of functionality of manufacturing system parameters when, as a consequence of its modernization a change in equipment of a certain section or a replacement of individual devices was planned. Such actions cause a necessity to determine the system’s operating efficiency and reliability after changing parameters as well as the impact of working processes on the product quality. Such actions were conducted as a result of performed research works no. KBN nr 8 T07 D 034 21 [5].